Cytomegalovirus esophagitis associated with arytenoid cyst in an immunocompetent host - Anchan, Shibani V.; Khialani, Anjali; Raj, Athira (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
CMV esophagitis is usually encountered in immunocompromised individuals and esophagus is rarely affected in immunocompetent individuals. CMV esophagitis associated with arytenoid cyst has not yet been reported in literature to the best of my knowledge and can be considered in case of recurrence of cyst following excision. The objective of this study is to report the unique presentation of CMV in an immunocompetent patient. A middle-aged immunocompetent lady presenting with dysphagia was diagnosed to have arytenoid cyst. Biopsy from upper esophagus revealed cytomegalovirus inclusion bodies and immunological test were performed to confirm the pathology. The cyst excision lead to recurrence. It was excised again followed by a course of intravenous ganciclovir. Currently, the role of antiviral in treatment of CMV esophagitis in immunocompetent individual is not well established. We have obtained good result in this patient with a course of Ganciclovir following excision of the cyst. The rarity of cytomegaloviral upper esophageal involvement, its association with arytenoid cyst and the utility of antivirus in treatment of an immunocompetent host makes this case report unique and interesting.